2020
DOI: 10.2478/medu-2020-0002
|View full text |Cite
|
Sign up to set email alerts
|

Improving Performance Together: Twinning Partnership Between Medium and Low Performer Districts in Ethiopia

Abstract: This article describes the United States Agency for International Development Transform: Primary Health Care Activity supported a twinning partnership strategy, which was implemented between districts (woredas) in the different performance categories. This study presents the details of the partnership and the result observed in health systems strengthening in Ethiopia. The twinning partnership strategy was implemented with six steps. The established relationship helps the health systems to build the skill and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 2 publications
2
2
0
Order By: Relevance
“…The case study revealed that the twining partnership strategy, which was adopted from the WHO’s twinning partnership for improvement, helps the performance of the district health system to accelerate transformation towards UHC. This finding was consistent with Bitton et al , (2017), Riggs et al , (2014), Corbin et al , (2012) and Argaw et al , (2020) recommendations for strengthening primary health care as a pathway towards UHC [ 21 , 28 30 ].…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…The case study revealed that the twining partnership strategy, which was adopted from the WHO’s twinning partnership for improvement, helps the performance of the district health system to accelerate transformation towards UHC. This finding was consistent with Bitton et al , (2017), Riggs et al , (2014), Corbin et al , (2012) and Argaw et al , (2020) recommendations for strengthening primary health care as a pathway towards UHC [ 21 , 28 30 ].…”
Section: Discussionsupporting
confidence: 88%
“…This result could have been achieved as a result of the synergy created between partner districts. This finding was in line with Argaw et al , 2020 who attest that, the twinning partnerships helps districts to work together and achieve a higher performance category within 18 months [ 21 ]. Similarly, Argaw et al, (2019) who confer that working against minimum standards improves the performance of primary health care entities in Ethiopia [ 5 ].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations